Fibroblast Growth Factor 21 Limits Lipotoxicity by Promoting Hepatic Fatty Acid Activation in Mice on Methionine and Choline-deficient Diets - Fisher, ffolliott M. (Gastroenterology, 2014)
BACKGROUND & AIMS: Nonalcoholic fatty liver disease (NAFLD) is a common consequence of human and rodent obesity. Disruptions in lipid metabolism lead to accumulation of triglycerides and fatty acids, which can promote inflammation and fibrosis and lead to nonalcoholic steatohepatitis (NASH). Circulating levels of fibroblast growth factor (FGF)21 increase in patients with NAFLD or NASH, so we assessed the role of FGF21 in the progression of murine fatty liver disease, independent of obesity, caused by methionine and choline deficiency. METHODS: C57BL/6 wild-type and FGF21-knockout (FGF21-KO) mice were placed on methionine- and choline-deficient (MCD), high-fat, or control diets for 8–16 weeks. Mice were weighed; serum and liver tissues were collected and analyzed for histology, levels of malondialdehyde and liver enzymes, gene expression, and lipid content. RESULTS: The MCD diet increased hepatic levels of FGF21 mRNA more than 50-fold and serum levels 16-fold, compared with the control diet. FGF21-KO mice had more severe steatosis, fibrosis, inflammation, and peroxidative damage than wild-type C57BL/6 mice. FGF21-KO mice had reduced hepatic fatty acid activation and β oxidation, resulting in increased levels of free fatty acid. FGF21-KO mice given continuous subcutaneous infusions of FGF21 for 4 weeks while on MCD diets had reduced steatosis and peroxidative damage, compared with mice not receiving FGF21. The expression of genes that regulate inflammation and fibrosis were reduced in FGF21-KO mice given FGF21, similar to those of wild-type mice. CONCLUSIONS: FGF21 regulates fatty acid activation and oxidation in livers of mice. In the absence of FGF21, accumulation of inactivated fatty acids results in lipotoxic damage and increased steatosis.